Humor (re)positioning ethnolinguistic ideologies: "You tink is funny?". (23rd April 2015) - Jaffe, Alexandra; Koven, Michèle; Perrino, Sabina; Vigouroux, Cécile B.; Da Silva, Emanuel
Abstract This article examines how essentializing ideologies of language and identity in Toronto's Portuguese ethnic market, constructed as monolingual and monocultural within the larger mainstream market of English-speaking Canada, provide the background for humorous sociolinguistic performances that playfully acknowledge, reproduce, and challenge ethnolinguistic stratification. After more than sixty years, the dominant spaces of the local Portuguese market continue to exclude most Portuguese-Canadian youth by rarely legitimizing the use of English, bilingual code-switching, or 'broken' or 'Azorean' Portuguese. By choosing YouTube as a space in which to engage audiences in ideologies of language and identity through performances of sociolinguistic caricatures, three young Portuguese-Canadian amateur comedians negotiate sociolinguistic boundaries with an ambivalent agency. The mocking performances are legitimized by the performers' in-group status and reveal, among other things, how a stigmatized variety of Azorean Portuguese and certain ethnolinguistic stereotypes can be reappropriated and reinforced relative to sociolinguistic hierarchies. (Language ideologies, ethnic humor, performativity, heteroglossia)*